(untitled) (Research, Society and Development, 2025)
Gestational diabetes mellitus (GDM) is a condition characterized by glucose intolerance that manifests during pregnancy, posing risks to both mother and fetus. This study aimed to analyze risk factors, diagnostic methods, treatment, and the main complications associated with GDM, while emphasizing the importance of appropriate monitoring for maternal-fetal health. A literature review was conducted based on scientific articles published in the last fifteen years, as well as guidelines from governmental health agencies. The research focused on studies addressing early diagnosis and treatment of GDM, in addition to the long-term impacts on maternal and neonatal health. The findings showed that early detection and proper management of GDM, through a combination of balanced diet, glycemic monitoring, and, in some cases, the use of insulin or oral antidiabetic drugs, are essential to prevent complications such as preeclampsia and fetal macrosomia. Patient education also proved to be crucial for therapeutic success. It is concluded that early intervention, combined with continuous follow-up during pregnancy, is indispensable for reducing the risks associated with GDM. Furthermore, the implementation of public policies to expand access to diagnosis and treatment is necessary to ensure better maternal and fetal health outcomes.